The New Economics of Religion - Sriya Iyer (Institute for the Study of Labor (IZA), 2015)
The economics of religion is a relatively new field of research in economics. This survey serves two purposes it is backward-looking in that it traces the historical and sociological origins of this field, and it is forward-looking in that it examines the insights and research themes that are offered by economists to investigate religion globally in the modern world. Several factors have influenced the economics of religion: (1) new developments in theoretical models including spatial models of religious markets and evolutionary models of religious traits; (2) empirical work which addresses innovatively econometric identification in examining causal influences on religious behavior; (3) new research in the economic history of religion that considers religion as an independent rather than as a dependent variable; and (4) more studies of religion outside the Western world. Based on these developments, this paper discusses four themes first, secularization, pluralism, regulation and economic growth; second, religious markets, club goods, differentiated products and networks; third, identification including secular competition and charitable giving; and fourth, conflict and cooperation in developing societies. In reviewing this paradoxically ancient yet burgeoning field, this paper puts forward unanswered questions for scholars of the economics of religion to reflect upon in years to come.
Keywords: Z12; 330; economics of religion